(untitled) (Research, Society and Development, 2023)
Objective: To relate smile type with gingival phenotype in patients at the Catholic University of Cuenca dental clinic. Methods: This is a cross-sectional descriptive observational study, which included clinical records made by the lead researcher, based on observational and clinical parameters. The type of smile was defined as high, medium, or low. The North Caroline periodontal probe transparency method was applied. It was applied to all those patients over 18 years of age with upper incisors inside the mouth and who were admitted to the No.1 dental clinic of the Catholic University of Cuenca from 14h00 to 16h00 during November 2022, according to the inclusion and exclusion criteria. Results: The total number of patients who attended dental care during the month of November was 83, of whom 32 had a high smile, 36 medium and 15 low. On the other hand, 66 patients had a thick phenotype, of which 34 had a medium smile and 17 had a thin phenotype. Conclusions: The medium smile prevailed in most patients at 43.3%, and thick gingival phenotype with 79.5%. Both factors were observed in the same patient in 40.9% of the cases. Therefore, this study helped us to determine the correlation between the average smile type and the thick gingival phenotype.